2013
DOI: 10.1175/jas-d-12-017.1
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Eyewall Formation and Eyewall Replacement Cycles in a Simulated Hurricane: Effect of the Net Radial Force in the Hurricane Boundary Layer

Abstract: Multiple secondary eyewall formations (SEFs) and eyewall replacement cycles (ERCs) are simulated with the fifth-generation Pennsylvania State University (PSU)-National Center for Atmospheric Research (NCAR) Mesoscale Model (MM5) at horizontal grid spacing of 0.67 km. The simulated hurricane is initialized from a weak, synthetic vortex in a quiescent environment on an f plane. After spinup and rapid intensification, the hurricane enters a mature phase during which the intensity change is relatively slow. Convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 75 publications
(92 reference statements)
4
22
0
Order By: Relevance
“…Moreover, other than Qiu et al (2010), it is found that there is no clear link between outer rainbands and the VRWs in our simulation, which means the environment, even far from the TC center, can be important for SEF. Our study also complements recent studies of Rozoff et al (2012), Huang et al (2012), Qiu and Tan (2013), and Wang et al (2013) in understanding the interplay and positive feedback between balanced and unbalanced dynamic processes in SEF. It is believed 1) that the development of the outer rainbands and the unbalanced boundary layer processes characterized by supergradient winds and convergence should be taken as a precursor of SEF and as a basis for predicting the SEF and 2) that the development of the outer rainbands and the coupled boundary layer processes should be taken into full consideration.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, other than Qiu et al (2010), it is found that there is no clear link between outer rainbands and the VRWs in our simulation, which means the environment, even far from the TC center, can be important for SEF. Our study also complements recent studies of Rozoff et al (2012), Huang et al (2012), Qiu and Tan (2013), and Wang et al (2013) in understanding the interplay and positive feedback between balanced and unbalanced dynamic processes in SEF. It is believed 1) that the development of the outer rainbands and the unbalanced boundary layer processes characterized by supergradient winds and convergence should be taken as a precursor of SEF and as a basis for predicting the SEF and 2) that the development of the outer rainbands and the coupled boundary layer processes should be taken into full consideration.…”
Section: Discussionsupporting
confidence: 83%
“…DeMaria et al (2014) note that for many time scales intensity change predictions robustly improved in recent years; however, gains were typically weaker and not robust at #48 h. Across time scales, events occurring within the tails of the TC intensity change distribution inherently have reduced predictability. While rapid weakening episodes not associated with landfall are becoming increasingly well understood because of processes associated with secondary eyewall development (e.g., Houze et al 2007;Rozoff et al 2008;Wang et al 2013) or environmental influences (e.g., Wood and Ritchie. 2015), rapid intensification (RI) episodes continue to lack causal consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2013) proposed that SEF arises from a feedback between inward-moving rainbands, the balanced response to their source of heat, and unbalanced dynamics. Wang et al (2013) proposed that a ''net'' radial force in the boundary layer is relevant in the process and Qiu and Tan (2013) emphasized the role of the asymmetric boundary layer. Kepert (2013) presented theoretical arguments, based mostly on linearized Ekman theory, to propose a feedback mechanism for secondary eyewall formation that involves a local enhancement of the radial vorticity gradient, frictional updraft, and convection.…”
Section: Introductionmentioning
confidence: 99%